Exchange Rates, Interest Rates, and the Risk Premium - Engel, Charles (American Economic Review, 2016)
The uncovered interest parity puzzle concerns the empirical regularity that high interest rate countries tend to have high expected returns on short term deposits. A separate puzzle is that high real interest rate countries tend to have currencies that are stronger than can be accounted for by the path of expected real interest differentials under uncovered interest parity. These two findings have apparently contradictory implications for the relationship of the foreign-exchange risk premium and interest-rate differentials. We document these puzzles, and show that existing models appear unable to account for both. A model that might reconcile the findings is discussed. (JEL E43, F31, G15)